The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.18357/jcs.v38i1.15436
|View full text |Cite
|
Sign up to set email alerts
|

Home Literacy Environment and English Language Learners’ Literacy Development: What Can We Learn from the Literature?

Abstract: Intended for educators and researchers in the field of early childhoodeducation working with children from immigrant families, this articlefirst briefly addresses the relationship between home literacy environment and English language learners’ literacy development in both their heritage language and English. Second, through surveying the literature, I identify three different areas in which a home literacy environment influences English language learners’ literacy development: (a) through language attitudes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In terms of the research question, all aspects of the home literacy environment were found, and each aspect described also gave detail of how the home literacy environment supports the TEYL. Each aspect of the home literacy environment was taken and adapted from the previous studies conducted by Shi (2013) and Park (2008). Both of them were parental belief and attitude towards literacy, literacy activities at home (between parent and students), and the availability of literacy sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the research question, all aspects of the home literacy environment were found, and each aspect described also gave detail of how the home literacy environment supports the TEYL. Each aspect of the home literacy environment was taken and adapted from the previous studies conducted by Shi (2013) and Park (2008). Both of them were parental belief and attitude towards literacy, literacy activities at home (between parent and students), and the availability of literacy sources.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the USA had highlighted the importance of HLE that stimulated the development of children's cognitive and language skills (Bradley, 1985;Farkas & Beron, 2004). Moreover, Shi (2013) stated that HLE supported English language literacy (ELL) and literacy acquisition on both heritage language maintenance and second language acquisition.…”
Section: Home Literacy Environment Support the Teylmentioning
confidence: 99%